Luxury Communist Jesus: Ideology, the Work Ethic, and the Antiwork Politics of Jesus. Issue 3 (3rd September 2015) - Sandford, Michael
Abstract : This article begins by outlining contemporary anti-work politics, which form the basis of Sandford's reading. After providing a brief history of anti-work politics, Sandford examines recent scholarly treatments of Jesus' relationship to work. An examination of a number of texts across the gospel traditions leads Sandford to argue that Jesus can be read as a 'luxury communist' whose behaviour flies in the face of the Protestant work ethic. Ultimately, Sandford foregrounds those texts in which Jesus discourages his followers from working, and undermines work as an 'end in itself', contextualising these statements in relation to other gospel texts about asceticism and the redistribution of wealth.